Pengaruh Kualitas Pelayanan Pre-Flight Gapura Angkasa terhadap Kepuasan Penumpang Maskapai Citilink di Bandar Udara Internasional Lombok - Rhaisatul Rindyani Putri; Irwina Meilani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to examine the effect of Gapura Angkasa's pre-flight service quality on passenger satisfaction of Citilink Airlines at Lombok International Airport. Service quality is crucial in the airline industry, as it directly affects passenger satisfaction — a reflection of their emotional response to the services received. A quantitative method was used, with data collected through questionnaires distributed to Citilink passengers in Yogyakarta who had flown via Lombok International Airport. The data were analyzed using simple linear regression, t-test, and coefficient of determination with the help of SPSS v.25. The results show that the t-value (22.321) is greater than the t-table (1.660), with a significance level of 0.000 < 0.05, indicating that the alternative hypothesis (Ha) is accepted. This means Gapura Angkasa’s pre-flight service has a positive and significant effect on Citilink passenger satisfaction. The coefficient of determination (0.834) indicates that 83.4% of passenger satisfaction is influenced by pre-flight services, with a very strong correlation (correlation coefficient of 0.914).